Analisis Kondisi Keuangan Pemerintah Kabupaten Di Kalimantan - Ika Kurnia Indriani; Melati Pramudita Lestari; Merry Triani (INVENTORY: JURNAL AKUNTANSI, 2020)
An assessment of the financial condition of district governments in Kalimantan will provide an early warning to implement good regional financial management, so that regional financial health can be maintained. An analysis of the financial condition of district governments on the island of Kalimantan  has never been carried out. The APBD is one of the stimuli used by district governments to encourage regional economic growth. Therefore, based on this phenomenon, it is necessary to analyze the financial condition of the district government in all regions of Kalimantan. This study uses a descriptive quantitative approach using the method of budget solvency, service solvency, and financial independence. The data used is secondary data, namely the 2014-2018 Budget Realization Report. The study population was 37 district governments on the island of Kalimantan. The research sample was 185 samples. The results of the research by the Government of Mahakam Ulu Regency which is located in East Kalimantan Province and Sekadau Regency in West Kalimantan Province have the highest budget solvency, while the solvency of Sambas Regency in West Kalimantan and Kutai Kartanegara in East Kalimantan has the lowest budget solvency. The best financial independence in all districts in Kalimantan was obtained by Penajam Paser Utara District in East Kalimantan and Lamandau District in Central Kalimantan. The lowest level of financial independence was obtained by Kayong Utara District, West Kalimantan and Mahakam Ulu Regency, East Kalimantan. Tana Tindung and Mahakan Ulu districts had the highest service solvency, while Kubu Raya and Sambas districts had the lowest solvency.Keywords; Budgetary Solvency; Financial Independence; Service-Level Solvency; and District Governments